Experimental infection of BALB/c mice with felid alphaherpesvirus 1 - Débora Scopel e Silva; Clarissa Caetano de Castro; Fábio da Silva e Silva; Fabiane Borelli Grecco; Renata Nobre da Fonseca; Geferson Fischer; Marcelo de Lima; Silvia de Oliveira Hübner (Semina: Ciências Agrárias, 2022)
Felid alphaherpesvirus type 1 (FHV-1) is an important cause of respiratory and ocular diseases in cats worldwide. Mice have been widely used to study the pathogenesis of several human and animal viruses, especially herpesviruses. This study aimed to verify whether BALB/c mice are susceptible to FHV-1 infection. The animals were intranasally inoculated with FHV-1 and their clinical signs were observed from 3 days post-infection (dpi). At 10 dpi, the animals were euthanized and the lungs, liver, spleen, and kidneys were collected for histopathological examination and quantitative polymerase chain reaction. The results showed that mice were infected with FHV-1 and reproduced several features of the disease observed in its natural host. Histological lesions and viral DNA were found in all sampled tissues, with a higher frequency of FHV-1 DNA copies detected in the lungs. All mice were seroconverted to FHV-1 at 7 dpi. To our knowledge, this is the first report of experimental infection of BALB/c mice with FHV-1. Our findings demonstrate that this murine model can contribute to our understanding of FHV-1 pathogenesis and may be useful for trials against this virus.